Something visible in Japanese - Ken Hiraiwa (Glossa, 2018)
A number of languages of the world show a striking change in word order when what is modified is an indefinite pronoun: the modifier necessarily appears postnominally (e.g. something visible vs. *visible something). English and French are examples of this ordering pattern. Japanese, a head-final language with exclusively prenominal modifiers, nevertheless exhibits the same order as English and French when indeterminate phrases (indefinite pronouns) are modified. I argue that although the modifier in such structures may appear to be a postnominal modifier of the preceding indeterminate phrase, it is actually a prenominal modifier of the following light noun n. I further propose that the English/French-type construction has the same underlying structure as the Japanese-type construction and that apparent differences follow from a difference in the composition of so-called indefinite pronouns: an indeterminate system versus a light-noun system.